Glucagon-like peptide-1 receptor agonists as a Therapeutic Option for Antipsychotic-Induced Obesity: A Review of Current Evidence - Natalia Gniaź; Aleksandra Górska; Wiktor Grela; Jagoda Niewiadomska; Daria Furtak; Dawid Tulej; Paulina Głogowska; Alicja Dziedzic; Dominika Marciniuk; Natalia Marko (Journal of Education, Health and Sport)
Introduction Obesity affects over 650 million adults worldwide and is a major risk factor for cardiovascular diseases and type 2 diabetes. Among those affected are patients treated with antipsychotics, such as clozapine and olanzapine, which often lead to significant weight gain, increasing the risk of metabolic syndrome. Recent advances with glucagon-like peptide-1 receptor agonists (GLP-1 RAs), including semaglutide and liraglutide, show promise in addressing antipsychotic-induced obesity by reducing weight and improving metabolic health.